Nasal septal turbinate: Cadaveric study - AKAKIN, DİLEK; KAYA, ÖZLEM TUĞÇE (OCEAN SIDE PUBLICATIONS INC, 2014)
Background: Despite the importance of its location, the functional behavior of the nasal septal turbinate (NST) is still not completely understood. Basic histological knowledge is still lacking. The aim of this study was to describe the histological features of the NST and to compare its morphometric features to those of the adjacent nasal septum and the inferior and middle turbinates. Methods: The study included 50 fresh cadavers. Excisional biopsy specimens of the NST with adjacent posterior septum were collected. In addition, mucosal and submucosal biopsy specimens were taken of the inferior and middle turbinates. Morphometric analysis was performed on five different tissue types: glandular elements, connective tissue stroma, arterial structures, and capillary or venous sinusoids. Results: The mean proportion of venous sinusoids was statistically lower in the nasal septum and NST than in the inferior and middle turbinate. The mean proportion of glandular tissues was higher in the NST than in other regions of the nasal cavity. The mean proportion of arterial tissue was lower in the nasal septum and the NST. Significantly fewer capillary elements were found in the inferior and middle turbinates than in the nasal septum and NST. The mean proportion of connective tissues was lower in the NST than in other regions of the nasal cavity. Conclusion: The similar histopathological cell distribution in the middle and inferior turbinate supported a function as an erectile organ, but the findings for the NST pointed to different functional properties of this region.
Keywords: SWELL BODY; VALVE